Fluoride concentration in drinking water in three areas in peninsular Malaysia / Shaharuddin MS … [et al.] - MS, Shaharuddin; I, Mohd Izam Syah; J, lrwan; M, Muhd Mursyidi; Syahrial, Dasrilsyah (2004)
A study on the concentration of fluoride in drinking water in three areas in Peninsular Malaysia, namely Kajang in Selangor, Kuala Kangsar in Perak and Pasir Mas in Kelantan was performed. The samples were taken from homes of respondents who participated in a dental fluorosis study in the said areas. Water samples were taken in triplicates for three consecutive days and were stored in pre-cleaned HDPE 250 mL bottles at a temperature under 4 C. A total of 2115 bottles of water samples were collected during the study. Analysis of fluoride was carried out using a direct reading spectrophotometer model HACH DR/2010 using the SPADNS method. Results showed that fluoride concentration in drinking water ranged from 0.35 to 0.81 mg/L in Kajang, 0.12 to 0.90 mg/L in Kuala Kangsar and 0.25 to 0.85 mg/L in Pasir Mas. These readings were lower but within the regulation issued by the Ministry of Health, Malaysia, which is between 0.5 to 0.9 mg/L. Issues such as dental caries elimination arise with the inadequate concentration of fIuoride in some samples of drinking water studied.